The impact of the Federal Reserve System’s interest rate channel on the components of aggregate demand - Brózda-Wilamek, Dominika (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Monetary policy decisions, through the process of transmission mechanism, affect the term structure of nominal interest rates as well as other asset prices, and thus influences aggregate demand (e.g. consumer spending and business investments) and price levels through these effects. The aspect of monetary transmission to various components of aggregate demand has been relatively little studied in the literature of the subject. Aim: The main aim of the study is to empirically investigate the effect of the Fed’s monetary policy on major components of aggregate demand over the past 35 years. To this aim, the scale and timing of the interest rate pass-through to economic activity have been examined. Results: The empirical findings showed that that between 1984 and 2019, the sensitivity of consumption and investment expenditures to interest rate impulses were different. Firstly, fixed investment spending accounted for a significant part that was responsible for the response of real GDP following an interest rate shock. Secondly, in the case of personal consumption expenditures, expenses for durable goods were more sensitive to changes in the Fed’s interest rate than spending on services and nondurable goods. In this way, the study expands the existing literature by reporting the effects of the Fed’s monetary policy on major components of aggregate demand over the past 35 years